Optimasi Penentuan Pemenang Pengadaan Tracker Antenna Menggunakan Metode Simple Additive Weighting (SAW) - Fauzhia Rahmasari; Fogot Endro Wibowo; Sandy Agung Pangestu (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa & Inovasi, 2021)
Procurement usually held in a conventional manner which brings direct stakeholders such as committee and bidders. Procurement of goods/services can be done electronically. Electronic procurement is the procurement of goods/services carried out using information technology and electronic transactions in accordance with statutory provisions. In this research will be made a decision support system to facilitate committee in process of determining the winner of procurement by using Simple Additive Weighting (SAW) methods. SAW methods is more favored because of its effectiveness in executing the completion time. There are some criteria which become to base decision, among others, administrative, technical, price, and qualification. Meanwhile, the alternative to used form companies which register as a participant (in this research there are 3 companies and partnerships). The final result in this research is PT. A as first ranks (the winner) with preference value 13,7778. PT. B in order to two (first backup) with preference value 10,7317, and PT.C in order to three (second backup) with preference value 9,7843.